The days of anna madrigal eaudiobook A novel. - Maupin, Armistead (Tales of the City, 2014)
Narrated by Kate Mulgrew New York Times Bestseller "Wonderful. . . . As compulsively readable and endearing as all the previous novels have been." — Booklist (starred review) Suspenseful, comic, and profoundly moving, The Days of Anna Madrigal, the ninth installment in Armistead Maupin's bestselling ""Tales of the City"" series, follows one of modern literature's most beloved and indelible characters—Anna Madrigal, the transgender landlady of 28 Barbary Lane—as she embarks on a road trip that will take her deep into her complicated past Now ninety-two, and committed to the notion of "leaving like a lady," Mrs. Madrigal has seemingly found peace with her "logical family" in San Francisco: her devoted young caretaker Jake Greenleaf; her former tenant Brian Hawkins and his daughter Shawna; and Michael Tolliver and Mary Ann Singleton, who have known and loved Anna for nearly four decades. Some members of Anna's family are bound for the otherworldly landscape of Burning Man, the art community in Nevada's Black Rock Desert where 60,000 revelers gather to construct a city designed to last only one week. Anna herself has another destination in mind: a lonely stretch of road outside of Winnemucca where the 16-year-old boy she once was ran away from the whorehouse he called home. With Brian and his beat-up RV, she journeys into the dusty troubled heart of her Depression childhood to unearth a lifetime of secrets and dreams and attend to unfinished business she has long avoided.